The effects of water-based insulation paint applied to laminate flooring panels on the thermal conductivity coefficient and adhesion resistance - Kabakci, Ali; Kesik, Haci İsmail (BioResources, 2020)
In an effort to reduce negative feedback resulting from temperature fluctuations, house floors are commonly laid with laminate flooring. The aim of this study was to study the thermal insulation properties and adhesion strength of the water-based insulation paint mixed with hollow glass spheres and applied onto the laminate flooring. The objective was to determine whether a prepared insulation paint mixture can be used instead of backing paper. For this purpose, two different laminate flooring samples were used. In the first case, the upper surface of the sample was coated with decorative paper and the lining surface was coated with backing paper. The upper surface of the second sample was coated with decorative paper and the lining surface was not coated with backing paper. Then, insulation paint mixture was applied 2, 4, or 6 times to the lining surfaces of both groups, and experimental results were obtained. As the number of layers was increased, the insulation mixture applied to the lining surfaces of the test samples was found to contribute positively to thermal insulation and adhesion resistance of specimens.